Investigation of α-3He resonances at relative energy 1<Ex<20 in threeparticles processes 9Be + 13C → 15C + α + 3He - V. Ostashko; M. Lattuada; M. Milin; O. Goryunov; A. Di Pietro; D. Miljanic; M. Zadro; A. Musumara; M.-G. Pellegriti; S. Romano; S. Tudisco; A. Tumino; et al. (Ядерна фізика та енергетика)
Two particles coincidences of identified 15C and unidentified particle from 9 13 Be C + collisions are analyzed as three particles exit channel 9 13 15 3 Be C C He (, ) α and 9 13 15 4 Be C C He (, ) τ . In spectrum of α −τ relative energy 7 Be well-known states with 7 ( ) E Be x = 4,7, 6,73 and 9,2 МeV are identified and other at 7 ( ) E Be x ~11,6, 13, (14,1), 15,7 and 18 MeV are also possible. Situation that states of 7 Be with 7 ( ) E Be x = 7,21 and ~ 10 МеВ are not observed in those reactions are explained their not α −τ cluster structure.